2019
DOI: 10.5137/1019-5149.jtn.25897-19.2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the preoperative uric acid level and neutrophil lymphocyte ratio on preoperative and postoperative visual pain scores in patients with lumbar disc hernia: a cross-sectional study.

Abstract: AIM:To determine the relationship between the serum urate (SU) level, neutrophil / lymphocyte ratio (NLR), and pain severity using preoperative and postoperative visual analogue scale (VAS) scores in patients with lumbar disc herniation (LDH). MATERIAL and METHODS:This single-center, cross-sectional study included 20 consecutive patients who were operated for LDH by the same surgeon. The patients'pre-and postoperative UA levels, NLRs, and intensity severity VAS scores were investigated. Preoperative magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
3
9
1
Order By: Relevance
“…Besides, it behaved wide range of effect mechanisms against pathogens, including phagocytosis, and the production of reactive oxygen species, proteases, and neutrophil extracellular traps formation ( Nathan, 2006 ). Our findings that neutrophils were up-regulated in IDD patients were consistent with previous research: a cross-sectional study about neutrophil/lymphocyte ratio (NLR) by Bozkurt, et al reported a significant correlation between NLR and pre- and post-operative VAS scores of IDD patients under surgery ( Bozkurt et al, 2019 ). As the largest avascular organ, IVD is considered as immune-privilege organ due to its special structure, accumulating evidences suggested the mechanism which limited immunocytes and immune mediators entering NP tissue in IVD could be defined as blood-NP barrier, a complex composition of physical and molecular factors ( Sun et al, 2020 ), while blood vessels were crucial channel of immunocytes infiltration ( Johnson et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, it behaved wide range of effect mechanisms against pathogens, including phagocytosis, and the production of reactive oxygen species, proteases, and neutrophil extracellular traps formation ( Nathan, 2006 ). Our findings that neutrophils were up-regulated in IDD patients were consistent with previous research: a cross-sectional study about neutrophil/lymphocyte ratio (NLR) by Bozkurt, et al reported a significant correlation between NLR and pre- and post-operative VAS scores of IDD patients under surgery ( Bozkurt et al, 2019 ). As the largest avascular organ, IVD is considered as immune-privilege organ due to its special structure, accumulating evidences suggested the mechanism which limited immunocytes and immune mediators entering NP tissue in IVD could be defined as blood-NP barrier, a complex composition of physical and molecular factors ( Sun et al, 2020 ), while blood vessels were crucial channel of immunocytes infiltration ( Johnson et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Bozkurt et al reported a moderate positive correlation between preoperative NLR and postoperative VAS scores. 15 The disparity between our findings and those of Bozkurt et al may be due to differences in our assessment of the outcome measures. Bozkurt et al used the VAS score at 6 months after surgery as their outcome measure and did not define a threshold improvement in VAS score that signifies that the patient benefited from the surgery.…”
Section: Discussioncontrasting
confidence: 93%
“…Recently, Yılmaz et al reported that NLR was an independent predictor in patients with lumbar disc hernia and low back pain [ 20 ]. Similarly, another study showed that preoperative and postoperative pain was more severe among patients with lumbar disc hernia and a higher NLR level, as an indicator of inflammation [ 24 ]. Dagistan et al found no significant difference between serum NLR and PLR levels of the LDH patients and healthy controls [ 25 ].…”
Section: Discussionmentioning
confidence: 99%